Analisis Kekuatan dan Umur Kelelahan (Fatigue Life) Terhadap Pondasi Crane SWL 3,6 Ton pada Kapal LCT 31 Meter dengan Metode FEM (Finite Element Method) - Achmad Masykurozi; Adi Wirawan Husodo; Benedicta Dian Alfanda (Proceedings Conference on Marine Engineering and its Application, 2023)
– LCT is are transport vessels that can approach platforms and jetties. LCT vessels are equippedwith cranes to facilitate the delivery and transfer of accommodation needs on the ship. Therefore, it isnecessary to plan a crane foundation that can withstand the weight of the crane itself and the load liftedby the crane. The 31-meter LCT ship suffered damage to the crane foundation due to static loads, so it isnecessary to replace the new crane foundation. In this Final Project, we will analyze the strength andfatigue life of the 3.6 ton SWL crane foundation on a 31-meter LCT ship in order to minimize the risk ofwork accidents and estimate the fatigue life of the new crane foundation. To complete this Final Project,the method used is the finite element method by creating a model in AutoCAD 2016 software and analyzingit in the finite element method software. The results of the analysis show that the von mises stress thatoccurs is 124.53 MPa, while the maximum deflection that occurs is 1.54 mm and the safety factor valueis 1.525. These stresses and deflections are in accordance with BKI rules because they do not exceed theallowable stress of 190 MPa and the allowable deflection of 2.75 mm. And for the estimated fatigue lifeof the crane foundation of 28.62 years.